Studi Pemikiran Pendidikan Islam Imam Al-Mawardi - Asral Wadi; Mulyanto Abdullah Khayr (Nian Tana Sikka : Jurnal ilmiah Mahasiswa, 2024)
Imam Al-Mawardi instructed a teacher to be sincere in carrying out his duties. Educating and teaching should be oriented towards higher goals. Teaching and educating is a scientific activity that has high value and position, which is not in harmony with the material. Imam Al-Mawardi forbids someone from teaching and educating based on economic/material world motives. The sincerity and awareness of a teacher is to teach awareness of the importance of the task, so that it will be motivated to achieve maximum results. A teacher will carry out his duties professionally, marked by several attitudes. First; always prepare everything necessary to support the teaching and learning process, secondly; a teacher who will keep his promises sincerely and complete his duties, third; the use of free time will be directed towards professional interests, fourth; perseverance and tenacity in work. A sincere teacher will realize the importance of perseverance and tenacity in achieving his task, fifth; high creativity and innovation, arising from awareness of the increasing demands and challenges of educational prospects.